Second metatarsal stress fracture in sport: comparative risk factors between proximal and non-proximal locations. Issue 8 (5th March 2007) - Chuckpaiwong, Bavornrit; Cook, Chad; Pietrobon, Ricado; Nunley, James A
Abstract : Background: Stress fractures of the second metatarsal are common injuries in athletes and military recruits. There are two distinct areas in the second metatarsal where stress fractures develop: one proximal (at the base) and the other non-proximal (distal). Diagnosis can be difficult, and there is a difference in prognosis and treatment of the two types of stress fracture. Therefore differentiation of fracture location is warranted. Differences in risk factors and clinical outcomes between proximal and non-proximal stress fractures have not been studied. Objective: To determine whether different risk factors and/or clinical outcomes associated with proximal and non-proximal stress fractures of the second metatarsal exist. Methods: Patients diagnosed with proximal stress fractures of the second metatarsal were included in the study. Retrospectively, an age-matched control group with a non-proximal stress fracture was selected for comparison. Statistical analysis involved bivariate comparisons of demographic variables and clinical measurement between the two groups. Results: Patients with proximal stress fractures were more likely to be chronically affected, usually exhibited an Achilles contracture, showed differences in length of first compared with second metatarsal, were more likely to experience multiple stress fractures, and exhibited low bone mass. In addition, a high degree of training slightly increased the risk of a non-proximal fracture, whereas low training volume was associated with a proximal stress fracture. Conclusion: The signs, symptoms and clinical findings associated with proximal metatarsal stress fractures are different from those of non-proximal stress fractures.